Consumption Dynamics under Time-Varying Unemployment Risk - Karl Harmenberg; Erik Ôberg (Copenhagen Business School (CBS), Department of Economics, 2019)
Private consumption demand falls in response to increased unemployment risk during a recession, as households increase their precautionary savings and postpone irreversible durable investments. The postponement effect is seven times as large as the precautionary-savings effect in a calibrated buffer-stock savings model. In consequence, anticipation of future unemployment risk is more important than realized unemployment shocks in accounting for durable expenditure dynamics during recessions, while the opposite is true for nondurables. The importance of anticipation of future unemployment risk also means that having many 'hand-to-mouth' households, who do not respond to changes in income risk, significantly dampens the demand response for durables to an adverse labor market shock. We find that the model elasticities of durable and nondurable expenditures with respect to unemployment risk are close to what we estimate in micro survey data.
hdl:10398/9748
Keywords: E21; E24; E32; J64; 330; household consumption; income risk; unemployment; business cycles